Touch in achieving a pedagogically relevant focus in classrooms - Routarinne, Sara; Heinonen, Pilvi; Karvonen, Ulla; Tainio, Liisa; Ahlholm, Maria (Social Interaction. Video-Based Studies of Human Sociality, 2020)
This article focuses on touch, talk and embodied resources as a means of directing participants’ attention to a focal point in a pedagogical task. The data are drawn from a corpus of approximately 150 hours of video-recorded lessons from primary and lower secondary classrooms in monolingual and multilingual settings in Finland. The data were scanned for episodes of touch that occurred between teachers and students in relation to an ongoing pedagogical agenda. Using multimodal conversation analysis, we identified a complex multimodal gestalt (CMG; Mondada 2014a) consisting of touch followed by a deictic pointing gesture that occurred within an ongoing pedagogical activity. We present three excerpts from different pedagogical contexts that involve such a CMG as a means of directing a recipient’s attention to a pedagogical task. The CMG is relevant for managing attention within an ongoing learning task. We show how this CMG provides parallel participation frameworks without competition for the speaker, and argue that it is a technique for bringing together the teacher, student and content in ways that encourage the recipient’s attention to the pedagogical content. This analysis contributes to the growing body of studies on haptic sociality, especially in the institutional context of education.